Why Official Bailouts Tend Not to Work: An Example Motivated by Greece 2010 - Chamley, Christophe P. (2012)
The authors use recent events in Greece to illustrate that official bailouts tend not to work when countries have fundamental fiscal ('insolvency') problems and construct a two-period numerical example to explain why this should not come as a surprise.